Turning the 'commodity curse' into a blessing: Africa as a pioneering front Africa and Energy Security: Global Issues, Local Responses - (:unkn) unknown (My University, 2008)
Conferencier invité. Conference Organised jointly by Institute for Defence Studies and Analyses (IDSA) International Peace Research Institute Oslo DSA
Keywords: African Research